Entrepreneurial Strategies in Institutional Changes: Tackling the Conflicts Between New and Old Rules - Wu, You (online, 2021)
Prior literature emphasizes that aligning with regulatory, normative, and cognitive institutional arrangements aids organizational formation, resource gathering, and performance. However, during institutional changes, the old and the new rules often coexist and interact, resulting in conflicting institutional arrangements. These conflicts create strategic dilemmas for entrepreneurs, but we don't have a systematic understanding of entrepreneurial strategies to tackle the conflicts. To address this gap, my dissertation focuses on three aspects: (1) adapting to the transition from old rules to new rules, (2) leveraging the new rules to replace the old rules, and (3) combining the new rules and the old rules. I examine these aspects in three empirical settings respectively: marketization, digitization, and tokenization. My first paper analyzes how entrepreneurs change growth strategies during China's institutional change from a government-dominated to a more market-based economy. My second paper draws on institutional intermediary and network tie formation literature to examine entrepreneurial fundraising strategies on online platforms rather than offline. My third paper draws on optimal distinctiveness theory to explore how blockchain entrepreneurs combine new and old elements in framing to balance differentiation and legitimation. Empirically, I use machine learning models to create measures from big data and econometric models to identify causal relationships. Overall, my dissertation contributes to institutional theory by examining entrepreneurial agency in tackling institutional pressure and contributes to strategy literature by analyzing the institutional effects on entrepreneurial strategies.
Keywords: Graue Literatur; Hochschulschrift; Conformity; Legitimacy; Decision making